Expression of the gene region prem-env of dengue virus type 2 in Pichia pastoris - Nguyet, Phung Thu; Hanh, Nguyen Hong; Khang, Dinh Duy; Hai, Truong Nam (Academia Journal of Biology, 2014)
The Dengue fever is one of the most serious illnesses in many tropical and subtropical countries. Laboratory tests are essential for diagnosis of the Dengue infection. The gene region preM-env of Dengue virus type 2 containing about 2000 bp was amplified by using the RT-PCR method from the infected cell and cloned in the pCR2.1 vector. This gene region was inserted in the pPIC9 vector for expression in the yeast cells. The electroporation was used to transfer the recombinant plasmid (pPIC-D2) into P. pastoris cells. The expressed full-length PrM-E gene in P. pastoris was identified by SDS-PAGE and Western-blot. It was shown that the recombinant protein with molecular weight of approximately 79 kDa excreted into the supernatant of culture when induced with 1% methanol after 3 days. The protein concentration expressed in P. pastoris was estimated of 0.1-0.2 mg/ml by the comparison with the molecular weight of the protein marker. The result of Western blot indicated that the recombinant protein PrM-E was able to bind with rabbit monoclonal antibody specific to Dengue virus type 2. The purified recombinant PrM-E protein will be applied for producing the diagnosis Kit of Dengue virus.